ANALISIS KESULITAN GAYA BELAJAR MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS COKROAMINOTO PALOPO PADA MATA KULIAH ANATOMI TUMBUHAN - khaerati; Sukmawati Syam; Eva Sohriati (Universitas Cokroaminoto Palopo, 2022)
Plant anatomy is a branch of botany that studies the complex internal structures of plants and their functions. The structure in plants includes the constituent tissues of the organs contained in the plant itself. Plant anatomy is a compulsory subject for biology education students at Cokroaminoto Palopo University in semester 4. This study aims to determine the learning style difficulties of Biology education students at Cokroaminoto Palopo University in Plant Anatomy Course. The population and sample in this study were 4th semester students of the biology education study program, using a total sampling technique. The technique of collecting data is using the results of the questionnaire on learning style difficulties. The data analysis technique uses data reduction, data presentation and conclusion drawing. The results of data analysis indicators of learning motivation are 58.15%, Interest is 58.77%, Attitude is 47.37%, School environment is 48.87% and Family environment is 57.64%. From the existing data, it can be seen that the students' interest in learning factors with the highest percentage and attitude